2020
DOI: 10.3390/ijms21030744
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Imaging of Tight and Adherens Junctions: Challenges and Open Questions

Abstract: The tight junction (TJ) and the adherens junction (AJ) bridge the paracellular cleft of epithelial and endothelial cells. In addition to their role as protective barriers against bacteria and their toxins they maintain ion homeostasis, cell polarity, and mechano-sensing. Their functional loss leads to pathological changes such as tissue inflammation, ion imbalance, and cancer. To better understand the consequences of such malfunctions, the junctional nanoarchitecture is of great importance since it remains so … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…To be noted, SRFM has also been widely applied to other cell communication structures, namely epithelial cell junctions such as tight junctions, gap junctions, adherens junctions, desmosomes, and hemidesmosomes [ 145 , 146 , 147 ]. The superior resolution of SFRM techniques has enabled the detection of nanoclusters and subdomains of junction proteins, which could not be revealed with confocal microscopy.…”
Section: Immune Synapsesmentioning
confidence: 99%
“…To be noted, SRFM has also been widely applied to other cell communication structures, namely epithelial cell junctions such as tight junctions, gap junctions, adherens junctions, desmosomes, and hemidesmosomes [ 145 , 146 , 147 ]. The superior resolution of SFRM techniques has enabled the detection of nanoclusters and subdomains of junction proteins, which could not be revealed with confocal microscopy.…”
Section: Immune Synapsesmentioning
confidence: 99%
“…Recent advances in single molecule localization microscopy (SMLM) have provided opportunities for a more in-depth assessment of TJ changes with high spatial resolution as recently illustrated in studies involving ZO-1 in human endothelial cells [ 25 ]. This approach allows for the use of monolayers grown in filters after being subjected to TER, dextran leakage measurements, and immunostaining for specific TJ molecules [ 25 , 26 ]. Combining these methods in one experimental setting should circumvent inter-experimental variations and allow for combined analyses of specific TJ expression and localization, functional studies, and single molecule cluster analyses in a matched manner.…”
Section: Introductionmentioning
confidence: 99%
“…Cadherins compose a family of cell surface proteins that, using the adherens junction as a basis, participate in cell-cell adhesion, an essential process in tissue morphogenesis and integrity [73]. A previous study reported that adherens junctions form defensive barriers and maintain ion homeostasis, and that their functional deficiency triggers ion imbalance and tissue inflammation [74]. In intestinal epithelium, the selective barrier formed by adherens junction supervises absorption of fluid and solutes [75].…”
Section: Discussionmentioning
confidence: 99%